THE COLORS OF SOIL AS A PARAMETER TO DELIMITATE THE ENVIRONMENT OF A PALM SWAMPY - Barbosa, Glauber Stefan; Maltoni, Katia Luciene [UNESP]; Panosso, Alan Rodrigo [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2019)
The palm swamps are arranged in the landscape in wetlands, which contribute to regulate the hydrological cycle of water courses supply. These areas are characterized by superficial streams and populated by Buritis (Mauritia flexuosa), typical palm of these environments. The soils in the palm swamp present indicative of pedoenvironmental conditions related to intense reduction processes of Fe, common in swampy areas where the reducing environment hinders the oxidation process. This study aims to evaluate the use of soil color parameter, associated with data from iron extracted with dithionite (Fe DCB), as indicator for delimitation of areas that comprise a palm swamp, producing subsidies to adequate the permanent preservation area surrounding the palm swamp, and as an indicator for delimitation of soils under water influence. The results pointed out the color GLEY 1, with values from 5 to 8 and chroma N, and colors 10Y, and 5Y with value and chroma varying among 5/1, 6/1, 7/1 and 7/2 as a useful tool for delimitation of palm swamp pedoenvironment, as well as 330 ppm of iron, since both indicate the occurrence of soils formation under hydromorphic or gley environments.
Keywords: Pedomorphological profile; Fe; Dithionite citrate bicarbonate; Wetlands